Analysis of fatty acids composition in marine fish (genus tenualosa) - Rafaizah, Bt Jalaludin (Universiti Malaysia Sarawak, UNIMAS, 2013)
The polyunsaturated fatty acids (PUFAs) were known for its function that can enhance human health. It is well known for its function that can reduce the cardiovascular diseases, improve the fetal development and much more. Therefore many researches had been done towards the PUFAs. Marine fish were known for its Omega 3 composition. Besides Omega 3, Omega 6 also one types of PUFAs that will give benefits towards the human health. DHA and EPA are the PUFAs that fall into the group of Omega 3. The extraction of the fish oil had been analysed using the Bligh and Dyers method. The composition of the extracted oil had been analysed using the Gas chromatography-Mass spectrometry. Therefore, the qualitative analysis of the composition of PUFA in the Tenualosa toli (Terubok) had been done. The Tenualosa toil (Terubok) obtained from the fisherman with enough information of the place of captured.